Operando Ultrasonic Monitoring of Lithium-Ion Battery Temperature and Behaviour at Different Cycling Rates and under Drive Cycle Conditions. Issue 4 (1st April 2022) - Owen, Rhodri E.; Robinson, James B.; Weaving, Julia S.; Pham, Martin T. M.; Tranter, Thomas G.; Neville, Tobias P.; Billson, Duncan; Braglia, Michele; Stocker, Richard; Tidblad, Annika Ahlberg; Shearing, Paul R.; Brett, Dan J. L.
Abstract : Effective diagnostic techniques for Li-ion batteries are vital to ensure that they operate in the required voltage and temperature window to prevent premature degradation and failure. Ultrasonic analysis has been gaining significant attention as a low cost, fast, non-destructive, operando technique for assessing the state-of-charge and state-of-health of Li-ion batteries. Thus far, the majority of studies have focused on a single C-rate at relatively low charge and discharge currents, and as such the relationship between the changing acoustic signal and C-rate is not well understood. In this work, the effect of cell temperature on the acoustic signal is studied and shown to have a strong correlation with the signal's time-of-flight. This correlation allows for the cell temperature to be inferred using ultrasound and to compensate for these effects to accurately predict the state-of-charge regardless of the C-rate at which the cell is being cycled. Ultrasonic state-of-charge monitoring of a cell during a drive cycle illustrates the suitability of this technique to be applied in real-world situations, an important step in the implementation of this technique in battery management systems with the potential to improve pack safety, performance, and efficiency: